Perceptions and outlook on intercropping coffee with banana as an opportunity for smallholder coffee farmers in Uganda - Jassogne, Laurence T.P.; Asten, Piet J.A. van; Wanyama, I.; Baret, P. (Informa UK Limited, 2013)
Coffee and banana are important cash and food crops in Uganda and the surrounding East African highland region. Production is dominated by smallholders that have limited arable land and often coffee and banana are intercropped. No significant research and development efforts have been undertaken over the last few decades on this coffee/banana intercropping system. Because recent studies suggest that this system could be a practice with high benefits to the farmers, we decided to study the perceptions of stakeholders along the coffee value chain starting with farmers. Perception analysis based on open-ended interviews following interview guides revealed that a major limitation for the sustainability of this system was poor soil fertility conditions. Perceptions on the benefits of intercropping differed little among coffee actors; that is, banana intercropping provides additional food and income from smallholders’ limited land and helps farmers reduce risks related to drought, pest/disease attacks and coffee price volatility. However, farmers’ desire to minimize risks does not match the objective of stakeholders higher up the coffee value chain to maximize coffee production. Furthermore, research by public institutes, both national and international, is primarily organized for single crops and not systems. We conclude that the institutional setting of the coffee sector hampers the promotion of intercropping, despite the benefits for the farmer.